Âge au premier mariage, contraception et mortalité infantile : influence sur l'évolution de la fécondité d'une population berbère du Haut Atlas marocain (vallée d'Anougal) - Mohamed Cherkaoui; Abdellatif Baali; Mohamed Kamal Hilali; André Sevin; Georges Larrouy; Émile Crognier; Gilles Boëtsch (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
The recent fertility trends within a traditional Berber population of the Western High Atlas mountains (Anougal valley) and the main factors responsible for these trends have been studied during three retrospective and complementary inquiries. Results showed that a demographic transition has started within the population. The decrease in fertility observed in all age classes is related to the increase of age at first marriage and the decrease in infant mortality. The modern contraceptive methods don’t seem to be responsible for the observed  transition.